Hydration Characteristics and Microstructure of Alkali-Activated Slag Concrete: A Review. (January 2023) - Fu, Qiang; Bu, Mengxin; Zhang, Zhaorui; Xu, Wenrui; Yuan, Qiang; Niu, Ditao
Graphical abstract: Abstract: Alkali-activated slag concrete (AASC) is a new green building material. The amount of CO2 produced by AASC is 1/5th of that produced by ordinary Portland cement concrete (OPCC). In addition, AASC promotes the reuse of slag and other wastes and saves resources. Furthermore, the scope of use of slag has been expanded. The progress of the research on the hydration characteristics, microstructure, interfacial transition zone, and pore structure of AASC based on the relevant literatures was analyzed and summarized in this study. The influences of the slag composition, the type and dosage of the alkali activator, and the curing conditions on the hydration characteristics and the microstructure of the AASC were discussed. Relatively few research results on the microstructure of AASC are available, and the relevant conclusions are not completely consistent. Moreover, there are many constraints on the development of AASC (e.g., complex composition of raw materials of slag, large shrinkage deformation, and low fluidity). Therefore, further research is required.